Anaerobic Fermentation of Mixed Fruits Peel Waste for Functional Enzymes Production Employing Palm Sugar and Molasses as The Carbon Source - Retnowati, Diah Susetyo; Kumoro, Andri Cahyo; Haryani, Kristinah (Department of Chemical Engineering, Faculty of Engineering, Universitas Diponegoro, 2023)
The daily abundant generation of fruit peel waste potentially triggers environmental problems if no appropriate management is performed. Besides, fruit peel waste can be a valuable source for functional enzyme production. This study aims to investigate the use of molasses and palm sugar as sugar source during anaerobic fermentation of banana and papaya peel waste to produce functional enzymes. The fermentation was subjected to biomass at various banana peels to papaya peels mass ratio for 3 months. The feed consisted of sugar:biomass:water, and their mass ratio was kept constant at 1:3:10. Both brown functional enzyme cocktails obtained from the fermentation using palm sugar and molasses as carbon source were acidic with pH of 3.7 and 4.4, respectively. The amylase, protease, and lipase activities of the functional enzyme cocktails was maximum when the biomass mixture contained four portions of banana peel and one portion of papaya peel. In addition, molasses was found to be the better sugar source than palm sugar for producing functional enzymes from aerobic fermentation peel fruits comprises banana and papaya peels. This study proved that fruit peel waste can be converted to valuable functional enzymes as one of the solutions of fruit peel waste management Keywords: anaerobic fermentation; carbon source; enzyme activity; functional enzyme; organic waste